HISTORY OF NATIONAL INSTRUMENTS (Academicia Globe: Inderscience Research, 2022)
This article describes in detail the works of encyclopedic scholars on music and their analysis, the history of Uzbek musical instruments, types of Uzbek instruments and their similarities and differences.